2001
DOI: 10.1111/j.1708-8240.2001.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Nightguard Vital Bleaching and Its Effect on Enamel Surface Morphology

Abstract: This in vivo study demonstrated that a 14-day regimen of NGVB using a 10% carbamide peroxide solution had minimal effect on the surface morphology of enamel and that the effects did not worsen over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
13

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 18 publications
2
18
0
13
Order By: Relevance
“…Also, methods of analysis are different among the studies, with protocols based on scanning electron microscope (SEM) analysis, [20][21]27,[30][31]34,36,38 microhardness tests, 9,11,14,36,38,40 profilometric techniques, 4,15,18,34,36,[38][39] plasma-atomic emission spectrometric analysis associated with chromatography, 37 infrared absorption spectroscopy correlated with x-ray analysis, 41 atomic force microscopy 10,28 and nanoindentation techniques. 5 Conversely, only a few studies have attempted to assess whitening effects in vivo, 22,26,29 usually based on the analysis of an enamel replica using SEM. These studies on enamel surface characteristics 22,26,29 are mainly based on the morphologically subjective assessments of the enamel surface, rather than on precise measurements of the enamel surface profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, methods of analysis are different among the studies, with protocols based on scanning electron microscope (SEM) analysis, [20][21]27,[30][31]34,36,38 microhardness tests, 9,11,14,36,38,40 profilometric techniques, 4,15,18,34,36,[38][39] plasma-atomic emission spectrometric analysis associated with chromatography, 37 infrared absorption spectroscopy correlated with x-ray analysis, 41 atomic force microscopy 10,28 and nanoindentation techniques. 5 Conversely, only a few studies have attempted to assess whitening effects in vivo, 22,26,29 usually based on the analysis of an enamel replica using SEM. These studies on enamel surface characteristics 22,26,29 are mainly based on the morphologically subjective assessments of the enamel surface, rather than on precise measurements of the enamel surface profile.…”
Section: Introductionmentioning
confidence: 99%
“…5 Conversely, only a few studies have attempted to assess whitening effects in vivo, 22,26,29 usually based on the analysis of an enamel replica using SEM. These studies on enamel surface characteristics 22,26,29 are mainly based on the morphologically subjective assessments of the enamel surface, rather than on precise measurements of the enamel surface profile. Since it has been demonstrated that in vitro alterations are more evident than in vivo alterations, 13 several studies support the hypothesis that factors, such as the remineralizing potential and the buffering ability of saliva, may counteract the adverse effects of whitening on the enamel surface.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of carbamide peroxide on enamel surface after bleaching was studied by investigators and found there is no alteration of the surface texture of enamel or slight increase in enamel porosity immediately following treatment which is reversed after 6 months as observed in follow up examination [21,22]. Lewinstein et al, observed a slight reduction in enamel surface microhardness following 35% carbamide peroxide treatment on human enamel which was completely reversed when treated with 0.05% fluoride solution [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated surface alterations in enamel with the bleaching agents, 12,13) and loss of calcium and changes in calcium/phosphate ratio after applying carbamide peroxide on enamel [12][13][14] . However, studies on the effect of bleaching gels on enamel surfaces with 10% carbamide peroxide addressed that bleaching gels caused only minimal effect on the surface morphology and enamel microhardness 4,12,[14][15][16] . Lai et al 17) reported in their study that 10% carbamide peroxide bleaching produced only slight enamel surface alterations and this etching effect was likely to be pH-dependent.…”
Section: ⅳ Discussionmentioning
confidence: 99%